COMORBIDITY AND SURVIVAL OF PATIENTS WITH CHRONIC KIDNEY DISEAS STAGE 5 D - I. M. Shifris; I.O. Dudar (Ukrainian Journal of Nephrology and Dialysis, 2017)
Annual expansion of dialysis population, high mortality, considerable expenses on specialized medical care are evoked the medical community to research comorbidities, that undoubtedly has an influence on course of chronic kidney disease VD stage (CKD VD st.) and prognosis.Aim. The aim of this study was to investigate the prevalence and structure of comorbid conditions in patients with CKDVD stage, and determinate the relation between comorbidities and survival rate in dialysis population.Materials and methods. It was studied the prevalence and structure of comorbidities among 204 patients with CKD VD st. (125 on hemodialysis [HD], 51 on peritoneal dialysis [PD], and 28 on hemodiafiltration [HDF]). All recorded concomitant diseases with its incidence data and coand polymorbidity indices were analyzed in consideration of renal replacement therapy (RRT). The survival rates were assessed in according with indices of comorbidity by Kaplan - Mayer methodology.Results. The performed analysis was demonstrated that in almost single patient had no mononosologicalpathology. The numbers of concomitant diseases were 3,55, 3,3 и 3,4 3,3per patient on HD, HDF and PD, respectively, without significant relation with RRT modality. In according with the study results the most common comorbid conditions, irrespective from RRT modality, were anaemia (88%), arterial hypertension (86%), and secondary hyperparathyroidism (40%). The proposed modified index of polymorbidities was revealed as the universal marker of survival rate in patients with CKD VD st.Conclusion. Thus the considerable prevalence of comorbid conditions in population ofpatients with CKD VD st. irrespective of RRT modality has significant negative effect on prognosis.